The enemy through the content of Internet sites interested in the so-called Arab Spring Descriptive analytical study comparing the contents of a sample of sites 2010 - 2016 - madasi, bouchra (Journal of Social Sciences and Humanities, 2021)
The Arab Spring revolutions overthrew four regimes. After the Tunisian revolution, the Egyptian January 25 revolution succeeded in toppling former President Muhammad Hosni Mubarak, then the Libyan February 17 revolution by killing Muammar Gaddafi and toppling his regime, the Yemeni revolution and toppling and killing Ali Abdullah Saleh, and in Syria continues against President Bashar al-Assad . As the Arab Spring has become an entry point to reassess international policies, Arab regimes and foreign relations in the Arab countries, on the one hand, and on the other hand, the Arab revolutions came to demand new freedom and democracy in the Arab region. The study aimed to know and explore the contents of blogs and websites about the Arab Spring and the enemy, and the study saw that the latter changed in the media of the Arab Spring, and in determining who is the enemy as it was in the past the enemy was the West and America and Israel, and blogs and websites became an important and dangerous tool To define the enemy, and became the main engine of the Arab street, and to confront the existing regimes, especially in the Arab countries that went through the revolution.